COVID-19 Course in Vaccinated Patients - Yu. P. Linets; S. V. Artyukhov; A. N. Kazantsev; T. Y. Zaitseva; L. V. Roshkovskaya; S. V. Sokolova; A. Y. Chikin; G. K. Yenova; S. B. Kondakov (Неотложная медицинская помощь)
Aim of study. To conduct a retrospective analysis of treatment outcomes for COVID-19 in unvaccinated and vaccinated patients.Material and methods. The present retrospective single-center study included 209 patients who were vaccinated in history and hospitalized at the City Aleksandrovskaya Hospital for infection with COVID-19 in the period from April 5, 2020 to July 9, 2021. The average period between vaccine administration and hospitalization was 18.0 ± 11.0 days. In all cases, a positive result of the polymerase chain reaction (PCR) for the presence of SARS-CoV-2 was obtained. These patients were included in Group 1. The comparison group included 475 unvaccinated patients with comparable lung tissue damage according to multispiral computed tomography of the chest (MSCT) and a positive PCR result for the presence of SARS-CoV-2, selected randomly over the same observation period.Results. The lesions of the lung tissue according to the results of chest MSCT upon admission of the group were comparable (p=0.55). All deaths were observed in the group of unvaccinated patients (n=46; 9.7%; p<0.0001). In all cases, the cause was an increase in multiple organ failure. In the same cohort of patients, there was a statistically significantly greater number of deep vein thrombosis of the upper and lower extremities (p=0.02). In the group of vaccinated patients (1st), arterial thrombosis of various location was not diagnosed, while in the 2nd group (comparison), this pathology was detected in every 10th patient. At the same time, thrombosis of the arteries of the lower extremities developed statistically more often (n=52; 10.9%; p><0.0001). This condition was accompanied by an increase in laboratory parameters of the inflammatory reaction and coagulopathy with the progression of lung tissue damage to the 3–4th degree according to the results of MSCT. However, in 37 (7.8%) cases, open thrombectomy was not possible, and on the first day after the operation, repeated thrombosis developed, followed by amputation of the limb. In 23 (4.8%) cases, a fatal outcome was observed. Conclusion Vaccination prevents the severe course of covid-19: the progression of pneumonia, coagulopathy, and inflammatory syndrome. In vaccinated patients, no deaths, pulmonary embolism were observed, which demonstrates the absence of a severe course of the disease. All arterial thrombosis associated with covid-19 develops in unvaccinated patients and is accompanied by a high incidence of repeated thrombosis, requiring subsequent amputation of the limb. The widespread introduction of vaccination will help reduce the severity of the course and prevent complications of the new coronavirus infection. Key words: COVID-19, novel coronavirus infection, thrombosis, SARS-CoV-2, vaccine>˂0.0001). In all cases, the cause was an increase in multiple organ failure. In the same cohort of patients, there was a statistically significantly greater number of deep vein thrombosis of the upper and lower extremities (p=0.02). In the group of vaccinated patients (1st), arterial thrombosis of various location was not diagnosed, while in the 2nd group (comparison), this pathology was detected in every 10th patient. At the same time, thrombosis of the arteries of the lower extremities developed statistically more often (n=52; 10.9%; p˂0.0001). This condition was accompanied by an increase in laboratory parameters of the inflammatory reaction and coagulopathy with the progression of lung tissue damage to the 3–4th degree according to the results of MSCT. However, in 37 (7.8%) cases, open thrombectomy was not possible, and on the first day after the operation, repeated thrombosis developed, followed by amputation of the limb. In 23 (4.8%) cases, a fatal outcome was observed.Conclusion. Vaccination prevents the severe course of covid-19: the progression of pneumonia, coagulopathy, and inflammatory syndrome. In vaccinated patients, no deaths, pulmonary embolism were observed, which demonstrates the absence of a severe course of the disease. All arterial thrombosis associated with covid-19 develops in unvaccinated patients and is accompanied by a high incidence of repeated thrombosis, requiring subsequent amputation of the limb. The widespread introduction of vaccination will help reduce the severity of the course and prevent complications of the new coronavirus infection.